Physico-Mechanical Properties of Processed Hydrogenated Vegetable Oil Matrices (The East and Central African Journal of Pharmaceutical Sciences, 2020)
The present study was aimed at improving the physico-mechanical properties of hydrogenated vegetable oil (HVO) matrices. HVO was processed with a variety of binders plus an auxiliary binder, stearic acid. The resulting formulations were fractionated into a variety of particle sizes while some were made into a fixed blend. Tensile testing and dissolution studies were carried out on the various compacts prepared. The' minimum amount of binder, PVP K-30, that imparted appreciable tensile strength to processed HVO matrices was about 7% w/w. At PVP K-30 concentrations above 7.5% w/w, the release sustaining characteristics of the matrix significantly depreciated (tcal> 5.13, ttab = 2.23, p=0.05), even though tensile strength significantly improved. Besides retaining the basic release sustaining characteristics of the matrix, PVP K-90 and Luviskpl proved to be a better binder than PVP K-30 (tcal=5.22, ttab=2.05, p=0.05) PVP K-30 and ,Luviskol produced tablets with the same release sustaining characteristics (tca1=0.05).. Large particles (500-710 p.m) produced compacts with the best release sustaining characteristics and tensile strength. The present study showed that the tensile strength of HVO matrices can be improved by processing the HVO with an auxiliary binder such as stearic acid. Controlled release efficiency and tensile strength of such matrices can be enhanced by using large particles, (500-710 gm), of the formulation.
Keywords: Hydrogenated vegetable oil, controlled release efficiency, tensile strength..